2019
DOI: 10.1063/1.5116659
|View full text |Cite
|
Sign up to set email alerts
|

Fast control of dissipation in a superconducting resonator

Abstract: We report on fast tunability of an electromagnetic environment coupled to a superconducting coplanar waveguide resonator. Namely, we utilize a recently-developed quantum-circuit refrigerator (QCR) to experimentally demonstrate a dynamic tunability in the total damping rate of the resonator up to almost two orders of magnitude. Based on the theory it corresponds to a change in the internal damping rate by nearly four orders of magnitude. The control of the QCR is fully electrical, with the shortest implemented … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…The instantaneous response of the damping rates to the applied voltages shows that we can control the dissipation on a timescale substantially shorter than 1 μs. The QCR can be operated even at timescales in the range of 10 ns [63]. Furthermore, the dependence of the damping rate on the pulse amplitude follows the theory, as shown in the inset.…”
Section: Experimental Observationssupporting
confidence: 53%
“…The instantaneous response of the damping rates to the applied voltages shows that we can control the dissipation on a timescale substantially shorter than 1 μs. The QCR can be operated even at timescales in the range of 10 ns [63]. Furthermore, the dependence of the damping rate on the pulse amplitude follows the theory, as shown in the inset.…”
Section: Experimental Observationssupporting
confidence: 53%
“…Note that since typically C tr is of the order of a few to several tens of fF, in designing the combined QCR-transmon system, it may be important to account for the coupling to the QCR, since in previous experiments C c ≈ 800 fF and C ≈ 10 fF [40,42,43,48]. With this notation, the Hamiltonian for the combined QCR-transmon system readŝ…”
Section: (B)] Consists Of a Single Josephson Junction With Josephson mentioning
confidence: 99%
“…[42], this model was found to describe accurately both the tunability of the resonator dissipation rate by orders of magnitude and the consequently induced Lamb shift of the resonance frequency. Reference [43] experimentally demonstrated that the QCR can be turned on/off in nanosecond time scale, which seems adequate for qubit initialization.…”
Section: Introductionmentioning
confidence: 99%
“…Adding a non-Hermitian component to a Hamiltonian does not only broaden the resonances and allow the eigenstates to decay, but the eigenmodes can merge with each other at exceptional points, which are topological defects where not only the eigenvalues are degenerate but also the eigenvectors are parallel to each other [1,[12][13][14][15]. The flexibility to engineer gain and loss in a controllable manner for example in optics, (opto)mechanics, plasmonics, superconducting quantum circuits, dissipative Bose-Einstein condensates, exciton-polariton condensates and cold atom systems [1,2,12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] have naturally raised the interest to study the symmetry and topology in non-Hermitian physics systematically [33][34][35][36][37] with potential applications for example in the design of topologically protected laser modes [38][39][40][41][42][43].…”
mentioning
confidence: 99%